Life after death the viola da gamba in Britain from Purcell to Dolmetsch - Holman, Peter 1946- (Music in Britain, 1600-1900, 2010)
New research throws light on the history of the viol after Purcell, including its revival in the late eighteenth century through Charles Frederick Abel